Preparation and application of a new catalyst to produce bio-oil from microalgae liquefaction - Yipeng, Wang; Ge, Nan; Wenjia, Wang; Jinglai, Zhang; Wei, Han (International Journal of Agricultural and Biological Engineering, 2017)
In this study, hydrothermal catalytic liquefaction method was adopted to produce bio-oil from microalgae. The influence of supported Ni-Catalysts doped neodymium (Nd) on the bio-oil yield from microalgae liquefaction was investigated, aiming to find the optimal preparation procedure of bio-oil. It proved that under the condition of a temperature of 270°C and a reaction period of 30 min, the bio-oil yield of hydrothermal catalytic liquefaction of spirulina powder could reach 55.1% by means of the catalyst prepared with 1 mol/L neodymium nitrate as the dipping solution after a calcination for 4 h at 800°C. In addition, the characterization on catalyst was discussed in this research. Keywords: catalyst, bio-oil, microalgae, catalytic liquefaction, spirulina powder DOI: 10.3965/j.ijabe.20171001.2599 Citation: Wang Y P, Nan G, Wang W J, Zhang J L, Han W. Preparation and application of a new catalyst to produce bio-oil from microalgae liquefaction. Int J Agric & Biol Eng, 2017; 10(1): 169–175.